Phosphate supplementation withdrawal during dry season for Nelore range cows - Nogueira, Ériklis; Nicodemo, Maria Luiza Franceschi; S' Thiago, Luiz Roberto Lopes de; Moraes, Sheila da Silva; Macedo, Manuel Cláudio Motta; Vieira, Jairo Mendes (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the reproductive performance of Nelore cows at 'Marandu' palisade grass paddocks, after dicalcium phosphate withdrawal from the mineral supplement in the dry season. Sixty breeding cows received, during six years, a complete mineral mixture in the wet season. In the dry season, the treatments consisted of: a complete mineral mixture (MMC); MMC without dicalcium phosphate (MM); and MM plus a concentrate. Pastures were managed in order to allow for adequate dry matter availability. The removal of dicalcium phosphate from the mineral supplement, during the dry season, did not affect the animal reproduction performance which was evaluated as pregnancy rates, delivery intervals and return of oestrous cycles. Cows receiving concentrate in the dry season had higher body score at delivery; primiparous cows which fed concentrate showed a lower number of days open, in comparison to the primiparous ones of the other treatments. Dicalcium phosphate withdrawal from the mineral supplement, source of phosphorus and calcium, during the dry season, does not affect the reproductive performance of multiparous range cows grazing 'Marandu' palisade grass.